Association between dietary inflammatory index and all-cause mortality risk in adults with coronary heart disease in the United States - Enyang Wang; Caoyang Fang; Jing Zhang; Yuqi Wang (Scientific Reports)
Abstract Diet and inflammation are crucial in the incidence and progression of coronary heart disease (CHD). This study aimed to investigate the correlation between the Dietary inflammatory index (DII) and all-cause mortality in CHD patients. A total of 1,303 CHD patients from the National Health and Nutrition Examination Survey (NHANES) between 2003 and 2018 were included. Multivariate Cox regression was used to explore the correlation between the DII and the risk of all-cause mortality in these patients. Restricted cubic spline (RCS) analysis was also utilized to examine the relationship between the DII and all-cause mortality risk in CHD patients. Additionally, subgroup analyses were conducted to determine how the correlation between the DII and all-cause mortality varied across different demographics. During a median follow-up period of 77 months among 1,303 CHD patients, 536 died from all causes. The DII scores were significantly higher in deceased patients compared to survivors. After adjusting for confounding factors, the multivariate Cox regression analysis indicated a strong positive correlation between the DII and all-cause mortality in CHD patients. RCS analysis suggested a non-linear relationship between the DII and all-cause mortality among CHD patients. Additionally, an increase in DII was more pronounced in its impact on female patients. The DII is strongly correlated with the risk of all-cause mortality among CHD patients, particularly among females. Thus, managing dietary inflammation is vital for the prevention and treatment of CHD, especially in female patients.